IL-38 restrains inflammatory response of collagen-induced arthritis in rats via SIRT1/HIF-1α signaling pathway. Issue 5 (28th May 2020) - Pei, Bing; Chen, Keyan; Zhou, Shenglai; Min, Dongyu; Xiao, Weiguo
Abstract: Objective: To observe the restraining effect of IL-38 on inflammatory response in collagen-induced arthritis rats (CIA), and to explore the regulatory mechanism of SIRT1/HIF-1α signaling pathway. Methods: 40 SD rats were randomly divided into Control group, CIA group, CLL group and CLH group, with 10 rats in each group; CIA rat model was established. The effects of IL-38 on arthritis index, inflammatory response, osteogenic factor and angiogenic factor were observed by methods including HE staining, ELISA, immunohistochemical and immunofluorescence. Human synoviocytes were cultured in vitro, and SIRT1 inhibitors were added to detect the expression for relating factors of SIRT1/HIF-1α signaling pathway by Western blot. Results: IL-38 could alleviate CIA joint damage and restrain inflammatory response, could up-regulate the expression of OPG in CIA rats and could down-regulate the expression of RANKL and RANK. IL-38 could restrain the expression of VEGF, VEGFR1, VEGFR2 and HIF. Moreover, we found that IL-38 could up-regulate the SIRT1 expression and down-regulate the HIF-1α, TLR4 and NF-KB p65 expression in CLL and CLH groups. From the treatment of synoviocytes to simulate the CIA model and the treatment of SIRT1 inhibitors, we demonstrated that the inhibitory effect of IL-38 on inflammatory factors and regulation of SIRT1/HIF-1α signaling pathway-related proteins were inhibited. Conclusion: IL-38 can restrain the inflammatory response of CIA rats, can promote the expression of osteogenic factors, can inhibit neovascularization, and can alleviate joint damage in rats. The mechanism may be related to the regulation of SIRT1/HIF-1α signaling pathway.